Pioglitazone-Mediated Attenuation of Experimental Colitis Relies on Cleaving of Annexin A1 Released by Macrophages - da Rocha, Gustavo Henrique Oliveira; de Paula-Silva, Marina; Broering, Milena Fronza; Scharf, Pablo Rhasan dos Santos; Matsuyama, Larissa Satiko Alcântara Sekimoto; Maria-Engler, Silvya Stuchi; Farsky, Sandra Helena Poliselli (Frontiers in Pharmacology, 2020)
Ulcerative colitis and Crohn’s disease are chronic inflammatory bowel diseases (IBDs) which burden health systems worldwide; available pharmacological therapies are limited and cost-intensive. Use of peroxisome proliferator activated-receptor γ (PPARγ) ligands for IBD treatment, while promising, lacks solid evidences to ensure its efficacy. Annexin A1 (AnxA1), a glucocorticoid-modulated anti-inflammatory protein, plays a key role on IBD control and is a potential biomarker of IBD progression. We here investigated whether effects of pioglitazone, a PPARγ ligand, rely on AnxA1 actions to modulate IBD inflammation. Experimental colitis was evoked by 2% dextran sodium sulfate (DSS) in AnxA1 knockout (AnxA1-/-) or wild type (WT) C57BL/6 mice. Clinical and histological parameters were more severe for AnxA-/- than WT mice, and 10 mg/kg pioglitazone treatment attenuated disease parameters in WT mice only. AnxA1 expression was increased in tissue sections of diseased WT mice, correlating positively with presence of CD68+ macrophages. Metalloproteinase-9 (MMP-9) and inactive 33 kDa AnxA1 levels were increased in the colon of diseased WT mice, which were reduced by pioglitazone treatment. Cytokine secretion, reactive oxygen species generation and MMP-9 expression caused by lipopolysaccharide (LPS) treatment in AnxA1-expressing RAW 264.7 macrophages were reduced by pioglitazone treatment, effects not detected in AnxA1 knockdown macrophages. LPS-mediated increase of AnxA1 cleaving in RAW 264.7 macrophages was also attenuated by pioglitazone treatment. Finally, pioglitazone treatment increased extracellular signal-regulated kinase (ERK) phosphorylation in AnxA1-expressing RAW 264.7 macrophages, but not in AnxA1-knockdown macrophages. Thus, our data highlight AnxA1 as a crucial factor for the therapeutic actions of pioglitazone on IBDs.